Does Audit Quality Mediate the Effect of Auditor Tenure, Abnormal Audit Fee and Auditor’s Reputation on Giving Going Concern Opinion? - Hapsoro, Dody; Santoso, Tiara Rani (International Journal of Economics and Financial Issues, 2018)
The increased fraud of financial statements shows the low role of external auditors in providing a quality audit report. The purpose of this paper is to analyze the effect of the length of the audit firm-client relationship, abnormal audit fees and auditor reputation on giving of going concern opinion mediated by audit quality. The sample consists of 185 firm years. Sample companies listed on the Indonesian Stock Exchange from 2012 to 2016. Data analysis techniques using SEM based PLS.The result of the indirect effect test shows that auditor tenure and auditor reputation have a positive effect on audit quality while abnormal audit fees has a negative effect to audit quality and audit quality has a negative effect on giving of going concern opinion. The results of this study also show that the company’s financial condition does not moderate the effect of audit quality on giving going concern opinion. Keywords: Audit Quality, Auditor Tenure, Abnormal Audit Fee, Auditor’s Reputation, Going Concern Opinion JEL Classifcation: M42